A recent update of the diagnostic methods for tuberculosis and their applicability in Indonesia: a narrative review (Faculty of Medicine Universitas Indonesia, 2019)
Tuberculosis (TB) is a major global problem, especially with the high prevalence of HIV-TB co-infection. Delayed diagnosis and continual transmission contribute to high mortality in Indonesia, which has the third highest incidence of TB in the world, after China and India. Therefore, early diagnosis is needed to reduce the number of cases and to administer therapy to prevent the transmission of bacteria. The diagnosis of TB remains a challenge in clinical practice due to poor sensitivity and the requirement of skilled staff in microscopic tests, the slow growth Mycobacterium in culture, and the low number of bacilli present in extrapulmonary TB. Despite being the golden standard for TB diagnosis, cultures require 2-8 weeks to grow. Other methods for diagnosing TB include interferon-gamma release assays and serologic tests such as the tuberculin skin test. Recently, the World Health Organization recommended the GeneXpert MTB/RIF assay for diagnosing TB. This review presents the current state of TB epidemiology and various methods for TB diagnosis. In particular, the paper provides an in-depth discussion about the GeneXpert MTB/RIF assay that has been made available recently in selected tertiary hospitals in Indonesia.